Un artesano - Croce, Rodolfo (2011)
El autor reflexiona sobre la obra del arquitecto y diseñador argentino.
Keywords: STICOTTI, ALEJANDRO; ARGENTINA; ARQUITECTURA; ESTUDIOS DE ARQUITECTURA; PROCESO CREATIVO; DISEÑO INDUSTRIAL